Analysis of a multipronged community development initiative in two distressed neighbourhoods. (10th April 2017) - Weaver, Russell; Knight, Jason
Abstract: This article evaluates a multipronged community development initiative in Buffalo, NY, United States. Specifically, the city's community-based 'clean sweep' programme deploys teams of public servants to distressed neighbourhoods to enhance public spaces and engage residents in discussion and/or action. Statistical analyses of a pivotal year of the programme show that property owners on targeted city blocks appeared significantly less likely to violate property codes after the intervention, relative to remaining owners in two separate study areas. These results suggest that the actions that constitute a 'clean sweep' might make for effective community development in some distressed urban locations.